Biomechanical Analysis of the Waist Movement of Taijiquan Based on Finite Element Method - Lei Zhao; Wenjing Chen (International Journal Bioautomation, 2018)
Finite element method is a calculation method that can comprehensively and objectively analyze the stress and strain of complex objects. It is mostly used in biomechanics research of human complex structure. In Taijiquan exercise, the waist drives the motion of the body, which adapts to the physical condition of human body. Hence, the waist plays an important role in Taijiquan exercise. This paper applied CT imaging method and CAD modeling to establish a finite element model of the L4-L5 segment to explore the effect of finite element method on the waist, taking two actions of standing with the waist relaxed and pushing hands as examples. It was found that when the movement of Taijiquan pushing hands deepened, the flexion of the waist increased and the muscular strength of the erector spine increased gradually. However, the muscular force of erectors under the same curvature gradually decreased with the increase of the follower force. The cancellous bone pressure was the largest in the standing state, which was about 1.9 MPa. With the increase of the curvatures, the cancellous bone showed a tendency of first decreasing and then increasing. The pressure in the lumbar disc was the lowest of all values in an upright position. With the deepening of pushing hand movements, the waist curvature becomes larger, the pressure inside the lumbar disc also became larger; in the case of the same curvature, the greater the follower forceb, the greater the pressure. Therefore, waist bending angle in Taijiquan exercise has an important impact on the spine strength and lumbar disc pressure.